2010
DOI: 10.3748/wjg.v16.i39.4932
|View full text |Cite
|
Sign up to set email alerts
|

HBx-induced reactive oxygen species activates hepatocellular carcinogenesisviadysregulation of PTEN/Akt pathway

Abstract: HBx induced ROS promoted Akt pathways via oxidized inactive PTEN. HBx and ROS maintained a positive regulatory loop, which aggravated carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…A large body of literature has documented that HBx localizes to the mitochondrial membrane and disturbs mitochondrial function (10,16,31,51,54), and the observation that HBx increases cellular ROS levels has been reported by many research groups (5,13,15,31,33,51,61). Additionally, recent work showed that cisplatin also triggers oxidative stress (21,46).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has documented that HBx localizes to the mitochondrial membrane and disturbs mitochondrial function (10,16,31,51,54), and the observation that HBx increases cellular ROS levels has been reported by many research groups (5,13,15,31,33,51,61). Additionally, recent work showed that cisplatin also triggers oxidative stress (21,46).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has revealed that ROS may play an important role in JNK-dependent autophagy regulation (46)(47)(48)(49), while HBx treatment has been reported to cause ROS generation in hepatoma cells (50,51). We thus investigated the role of ROS in HBx-induced JNK activation and the ensuing autophagosome formation.…”
mentioning
confidence: 99%
“…HBx of genotype D HBV causes hypermethylation of the gene promoter of glutathione Stransferase GSTP1, which is a candidate enzyme for protecting cells against ROS with www.intechopen.com related toxic products (Niu et al, 2009). In turn, ROS stimulate HBx expression (Ha et al, 2010), suggesting that ROS may be an autocrine transducer of HBx-mediated carcinogenesis. Very recently, HBX was shown to activate the transcriptional activity of Forkhead box class O 4 (Foxo4) via JNK, leading to enhancement of the resistance to oxidative stress-induced cell death (Srisuttee et al, 2011).…”
Section: Hbv and Rosmentioning
confidence: 99%